Kajian Perilaku Kepatuhan Medikasi Pasien Tuberculosis Paru di Kabupaten Ngawi: Sebuah Model Matematis - Kartini, Puri Ratna; Norachuriya, Zedny; Novitasari, Karisma Surya; Shintawati, Shefina; Wisnubroto, Agung Praboow (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2024)
Background: Tuberculosis (TB) is currently still a health issue in Indonesia. Indonesia is the country that contributes the second largest number of tuberculosis cases after India. Ngawi is one of the cities in East Java Province with a large number of tuberculosis cases. In 2022, tuberculosis cases in Ngawi Regency will double from the previous year with the death rate also increasing from the previous year. This shows that tuberculosis control in Ngawi Regency has not been effective. Efforts are needed to increase medication compliance in tuberculosis sufferers so that therapeutic success can be achieved so that the death rate and tuberculosis transmission rate can be reduced.Methods: This research is an analytical observational study with a cross sectional research design which aims to create a mathematical model of medication adherence in pulmonary TB sufferers in Ngawi Regency. This research involved 102 pulmonary TB sufferers at Dr. Soeroto Hospital, Widodo Hospital and Ngawi Regency Health Center. Pulmonary TB sufferers were selected using a purposive sampling technique. Data were analyzed using multiple logistic regression tests.Result: Based on interviews conducted with 102 respondents, the results obtained were that the variables age, length of treatment, motivation to recover, self-perception, knowledge, access to health facilities, medication assistance, family support, drug side effects and health facility administration were candidates for bivariate testing.Conclusion : The variables of self-perception, knowledge, family support and health facility administration are the dominant factors influencing medication compliance in pulmonary TB sufferers in Ngawi Regency in 2023.